PEMIKIRAN HAMKA TENTANG GURU PROFESIONAL DALAM TAFSIR AL-AZHAR - Thaufan Fathulloh; Agus Supriyanto (Turats, 2022)
The professional predicate in being a teacher is a competency that needs to be fulfilled for each teacher in carrying out his obligations and responsibilities, namely teaching and educating as well as in carrying out other activities. This is because professional competence is often neglected so that the education process does not run optimally, such as a teacher who cannot master the material, concepts, and knowledge he will teach his students. Then in life in the era of globalization, of course, for a teacher to be able to answer all the challenges and problems that will occur at that time so that c can still achieve the ideals in education by prioritizing his professionalism. This research uses a descriptive qualitative method with a character study approach, including the character's thoughts. At the same time, the focus is on research on Hamka's thoughts about professional teachers in his book Tafsir Al-Azhar. The results obtained in this study indicate that, according to Hamka, the nature of professionalism is a requirement that must be owned and controlled by a teacher so that students can have faith in the Creator, broad knowledge, and noble and personal character that provides benefits to society. Because teachers are role models and examples for students in the classroom, therefore s should not carry out this teaching profession by just anyone. The other results indicate that Hamka has dynamic thinking with the laws applied to today's education. For example, Hamka has reminded us that a teacher must always be ready to keep up with the times that will always occur and their correlation with the current situation of the teacher. Can involve electronic devices in learning.